Control efficiency improvement of an electro-hydraulic winch - Duțu, I.C.; Frățilă, C.; Axinte, T.; Munteanu, M.G.; Calancea, L.; Diaconu, M.; Drăgan, C. (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
The paper presents a study regarding electro-hydraulic control systems for drive winches, a structural part of LARS (Launch and Recovery Systems). In the Introduction section of the paper, the authors present the domains of the research vessel. Furthermore, there is presented the importance of launch and recovery systems (LARS) and drive winches on the deck of a research vessel. The launch and recovery systems (LARS) using drive winches are installed on the stern of the research vessel. Further in the paper, the authors present the results of studying three simplified systems that use electric, hydraulic and electro-hydraulic driving solutions. Furthermore, there are presented comparative advantages of using this three types of drive winches. At the end of the paper, the authors perform an analysis of the electro-hydraulic systems for the drive winch, using a modelling and simulation software. Each schematic is presented along with its components. Moreover, the authors mention that all the schematics presented in this paper are modelled using FluidSim software from FESTO. In this case, only three mathematic relations are used in the paper: the Cauchy momentum (convective form), the incompressible Euler relations and the pressure losses in the hydraulic and electro-hydraulic drive winch.